The Relationship Between Mother's Age at Childbirth and the Incidence of Low Birth Weight (LBW) at PKU Muhammadiyah Yogyakarta Hospital In The Years 2017-2021 - Mariya Ulfa Damayanti; Umam, Nurcholid; Agustin, Helfi (Ahmad Dahlan Medical Journal, 2023)
Low Birth Weight (LBW) is a critical health issue, particularly in developing countries with low socio-economic conditions. The World Health Organization (WHO) reveals that more than 80% of 2.5 million babies born worldwide each year experience deaths due to LBW. Indonesia falls into the category of countries with a significant incidence of LBW in the Southeast Asian region. In 2019, the highest Infant Mortality Rate (IMR) in Indonesia was linked to LBW cases. This research adopts a quantitative approach with an observational analytic design, focusing on the analysis of relationships between variables. The research method used is a cross-sectional approach. The study was conducted at RS PKU Muhammadiyah Yogyakarta in June 2023. The sampling method applied is non-probability sampling with purposive sampling variations. The research findings indicate a significant relationship between the age of mothers during childbirth and the incidence of LBW (p-value = 0.000). Rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1) depict a strong association between the age of mothers during childbirth and LBW incidents. The results of the Odds Ratio (OR) analysis show a figure of 10.427. Overall, this research concludes that a significant relationship exists between the age of mothers during childbirth and the occurrence of LBW. These findings highlight the potential impact of maternal age during childbirth on the risk of LBW in newborns.     This is an open access article under the CC–BY-SA license.